Online Training on How to Produce Hygienic Tempeh during the Covid-19 Pandemic - Tati Barus; Rory Anthony Hutagalung; Rianita Pramitasari; Vivitri Dewi; Alfonsus Samuel Satya Pradipta (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
One of the Indonesian government's strategies to control the spread of the Covid-19 virus is to restrict people’s mobility when going out, which is often called the Implementation of Restrictions on Social Activities (PPKM). As a consequence of this PPKM, access to sufficient food tends to be rather limited. One effort to help people meet their food needs was through online tempeh-making training. This training, conducted online using Zoom and WhatsApp groups, involved community members who were connected through several health-related WhatsApp groups. The participants were all Indonesian from various areas, including the Greater Jakarta area, Ambon, Makassar, Medan, Padang, and even the US. Most of them were over 40 years old and were either employees or college graduates. Considering the significance of tempeh as a food item in Indonesia and a relatively affordable source of protein, the training became relevant in helping the participants to produce their own tempeh at home amidst the Covid-19 pandemic. After the training, all participants were found to be able to make tempeh with good quality and hygiene, with several participants even exhibiting creativity in processing their tempeh into more advanced tempeh products, such as tempeh noodles, tempeh pudding, and tempeh steak. In addition, their positive perception of tempeh as a healthy food item increased after attending the training.